Model Team Games Tournament (TGT) dalam pembelajaran Matematika pada kemampuan berhitung siswa Sekolah Dasar - Selvi nur santi; Ruli Setiyadi; Anugrah Ramadhan Firdaus; Ryan Dwi Puspita (IKIP Siliwangi, 2026)
This research is to study theoretically the Team Games Tournament model in mathematics learning in elementary school students' numeracy skills. The method in this research is a literature study and the sample comes from five articles published in national journals. Then the results of this study are influential to determine the implementation of the Team Games Tournament model in mathematics learning on the numeracy abilities of elementary school students. The results of the study in this study showed that there was an increase in the ability of students to understand mathematics concepts after using the Team Games Tournament model. The increase in applying the Team Games Tournament model of learning provides a significant increase in understanding, the Team Games Tournament learning model is better than learning using the conventional model, because in the ongoing learning process it can create a pleasant learning atmosphere and students are not afraid to issue opinions so that the Team Games Tournament model indirectly can also increase the interest in learning elementary school students towards mathematics.